1999
DOI: 10.1038/sj.gt.3300841
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the murine interleukin-12 gene in vivo by a Semliki Forest virus vector induces B16 tumor regression through inhibition of tumor blood vessel formation monitored by Doppler ultrasonography

Abstract: To elucidate further the potential of a Semliki Forest virus IL-12 genes induced tumor regression, the antiangiogenic-(SFV) vector in vivo for gene therapy, we constructed a activity of SFV-IL12 was investigated using Doppler ultravector, SFV-IL12, to transfer murine IL-12 genes into sonography (DUS). SFV-IL12 inhibited in situ neovascutumors. A single intratumoral injection of established B16 larization within the tumor, without affecting the resistance murine melanoma with SFV-IL12 resulted in a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
2

Year Published

2000
2000
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 46 publications
3
64
2
Order By: Relevance
“…A third antitumour mechanism that may operate is the inhibition of tumour angiogenesis by IL-12, which has been demonstrated in a previous study of tumour treatment by an IL-12-expressing SFV vector. 18 In the present study, the increased levels of the antiangiogenic chemokine IP-10 in the blood of treated mice, allied to the frequent occurrence of thrombosis and haemorrhage in the treated tumours, suggests that inhibition of angiogenesis also played a role in our model system.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…A third antitumour mechanism that may operate is the inhibition of tumour angiogenesis by IL-12, which has been demonstrated in a previous study of tumour treatment by an IL-12-expressing SFV vector. 18 In the present study, the increased levels of the antiangiogenic chemokine IP-10 in the blood of treated mice, allied to the frequent occurrence of thrombosis and haemorrhage in the treated tumours, suggests that inhibition of angiogenesis also played a role in our model system.…”
Section: Discussionsupporting
confidence: 57%
“…[23][24][25] Previous studies have shown that the amount of IL-12 available at the tumour site is critical for tumour regression, since it determines the number and type of infiltrating leucocytes. 21 It may also mediate the antiangiogenic effect of IL-12, 18 although the relative contribution of these two effects to the antitumour activity of IL-12 is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Direct intratumoral injection of these SFV/IL-12 particles in mice significantly inhibited growth of established B16 melanomas and inhibited neovascularization. 39 Recently, the application of alphavirus replicons has been extended to naked nucleic acids. 40 The relatively high efficacy of self-replicating nucleic acids as compared with DNA vaccines applied in anticancer therapies was correlated with the apoptosis-inducing features of the RNA replicase [41][42][43] and was attributed to mimicking of a viral infection that may trigger danger signals.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, these were concerned with the stimulation of an anti-tumour immune response 6 -8 or to inhibit angiogenesis through the expression of IL-12. 9 It has also been shown that the induction of p53-independent apoptosis by the SFV vector is an inherent function of the vector RNA and not dependent on expression of cloned heterologous genes. 10 Targeting of alphavirus vectors has been shown to be feasible, although only 1 targeting strategy has so far been described for alphavirus vectors, based on coupling of a monoclonal antibody to a viral spike protein via a protein A sequence.…”
mentioning
confidence: 99%